Wysokościowy obrzęk płuc oraz wysokościowy obrzęk mózgu w chorobie wysokogórskiej - rozpoznanie, postępowanie i leczenie = High altitude pulmonary edema and high altitude cerebral edema in high-mountain disease - diagnosis, proceedings and treatment - Siminska, Joanna; Przybylska, Sara; Ratuszek–Sadowska, Dorota; Siedlecki, Zygmunt; Grzyb, Sebastian; Nowacka, Krystyna; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Siminska Joanna, Przybylska Sara, Ratuszek–Sadowska Dorota, Siedlecki Zygmunt, Grzyb Sebastian, Nowacka Krystyna, Hagner Wojciech. Wysokościowy obrzęk płuc oraz wysokościowy obrzęk mózgu w chorobie wysokogórskiej - rozpoznanie, postępowanie i leczenie = High altitude pulmonary edema and high altitude cerebral edema in high-mountain disease - diagnosis, proceedings and treatment. Journal of Education, Health and Sport. 2016;6(11):390-397. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.168416 http://ojs.ukw.edu.pl/index.php/johs/article/view/4012 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 24.11.2016. Wysokościowy obrzęk płuc oraz wysokościowy obrzęk mózgu w chorobie wysokogórskiej - rozpoznanie, postępowanie i leczenie High altitude pulmonary edema and high altitude cerebral edema in high-mountain disease - diagnosis, proceedings and treatment Joanna Siminska1, Sara Przybylska2, Dorota Ratuszek – Sadowska1, Zygmunt Siedlecki3, Sebastian Grzyb3, Krystyna Nowacka1, Wojciech Hagner1 1 Katedra i Klinika Rehabilitacji Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu 2 Studenckie Koło Naukowe Dydaktyki Ratownictwa i Fizjoterapii Pourazowej Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu 3 Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie W obecnych czasach dość dużą popularnością cieszy się wspinaczka wysokogórska. Coraz więcej osób chce zostać zdobywcami wysokich szczytów. Zapominają przy tym o odpowiednim przygotowaniu i zachowaniu zasad które nierzadko kończą się pojawieniem u nich choroby wysokogórskiej oraz towarzyszącym jej wysokościowemu obrzękowi płuc i wysokościowemu obrzękowi mózgu. Wszystkie trzy choroby związane są z niewłaściwą adaptacją organizmu do ciśnienia panującego na dużych wysokościach. Pojawiają się symptomy które początkowo bagatelizowane z czasem stają się stanem zagrożenia życia. Chcąc w bezpieczny i odpowiedni sposób zdobyć coraz to wyższe pułapy należy odpowiednio przygotować się do tego. Należy także poznać podstawowe objawy chorób które mogą się pojawić oraz czas i wysokość w jakiej występują. Słowa klucze: choroba wysokogórska, wysokogórski obrzęk płuc, wysokogórski obrzęk mózgu. Abstract In the present time quite popular is climbing. More and more people want to be winners of high peaks. Forget the right preparation and principles which often end with the advent of high-mountain disease with them, and accompanying it high altitude and high-mountain of the brain. All three diseases are related to incorrect adaptation of the body to the pressure of high altitudes. Appear symptoms that initially underestimated the time become a life-threatening condition. If you want to in a safe and appropriate manner to get ever higher ceilings you should prepare for this. You must also learn basic symptoms of diseases that can occur, and the time and the amount in which they appear. Key words: disease of the Alpine mountain, pulmonary edema, high mountain swelling of the brain.